Dynamic team capabilities and their effect on team performance. - Teo, Seow Tian. (2012)
As today’s world is becoming increasingly dynamic and teams are becoming increasingly important in the organizational context, it is important to examine how a team’s dynamic capabilities influence their performance in a dynamic environment. Current research on dynamic capabilities largely focused on exploring it at the organizational level, with little extension beyond that to the team level, where dynamic capabilities are prevalent. The set of dynamic team capabilities tested in this study include Diversity, Presence of Leadership, Communication Frequency and Cohesiveness. A multiple linear regression model was employed to examine the effects these dynamic team capabilities have on team performance. After controlling for Team Strategy Planning and Length of Game, we found that under dynamic situations, the presence of a leader as well as diversity in the team significantly improves team performance. In other words, having a leader provides strategic guidance and diversity within the team brings greater flexibility, creativity and responsiveness to the team. This in turn improves team performance under dynamic conditions. This suggests that both of these elements are essential building blocks of dynamic team capabilities, where in a dynamic scenario, helps teams cope with complexity and potential confounds under time constrained environments.